Auxetic Foams for Sport Safety Applications. (2015) - Allen, Tom; Martinello, Nicolo; Zampieri, Davide; Hewage, Trishan; Senior, Terry; Foster, Leon; Alderson, Andrew
Abstract: Auxetic materials offer potential to be applied to sports safety equipment. This work reports quasi-static and impact testing of auxetic open-cell polyurethane foam - fabricated with a compression and heat treatment process - in comparison to its conventional counterpart. The foam was compressed to 70% of its original dimension along each dimension during the conversion process. Quasi-static compression testing confirmed the converted foam to be auxetic, with a Poisson's ratio of -0.08. Impact testing was performed for energies up to 5.6 J with an instrumented drop rig and high-speed video. Peak accelerations were ∼3 times lower for the auxetic foams, because they prevented bottoming. This work has shown further potential for auxetic foam to be applied to sports safety devices. Future work should look to optimise foam selection and the conversion process, while comparing auxetic foam with existing materials and products.